Effects of Water Temperature and Depth on the Catch Rate and Catch per Unit Effort for Mirror Carp (Cyprinus carpio) caught by Gillnets - Dartay, Murside; Atessahin, Tuncay; Duman, Erdal (Zoological Soc Pakistan, 2017)
This study was conducted in Keban Dam Lake (38 degrees 49.271'N - 39 degrees 17.057'E) between July and March 2012 in Elazig, Turkey. In this study examined variations in CPUE fishing values of mirror carp (Cyprinus carpio) according to different hanging ratios (E=0.5, 0.67), materials (multi-monofilament and multifilament), water temperature, and water depth. CPUE values were found to be higher at 24.5 degrees C water temperature and 13.7 m water depth with multi-monofilament gillnets with a result of 15.23 g/m, and the lowest was with multifilament gillnets with a result of 3.95 g/m (0.5); however, multi-monofilament gillnets had a result of 23.28 g/m and multifilament gillnets 14.58 g/m (0.67) in July, respectively. Depending on the water temperature and the water depth, the CPUE values were higher in July than the other months. The lowest CPUE value was in March with 11.5 degrees C water temperature and 18.5 m water depth. Finally, these findings clearly show that increasing and/or higher temperatures supported higher CPUE values. In contrast increasing depths gave rise to a decrease in CPUE values.
Keywords: Cyprinus carpio; Mirror carp; Cpue; Multi-monofilament; Multifilament